Spatial Assessment of Indices for Characterizing the Erosive Force of Rainfall in El Salvador Republic - Silva, Alexandre Marco da [UNESP]; Wiecheteck, Marcelo; Zuercher, Benjamin W. (Mary Ann Liebert, Inc., 2011)
Soil erosion data in El Salvador Republic are scarce and there is no rainfall erosivity map for this region. Considering that rainfall erosivity is an important guide for planning soil erosion control practices, a spatial assessment of indices for characterizing the erosive force of rainfall in El Salvador Republic was carried out. Using pluviometric records from 25 weather stations, we applied two methods: erosivity index equation and the Fournier index. In all study area, the rainiest period is from May to November. Annual values of erosivity index ranged from 7,196 to 17,856 MJ mm ha(-1) h(-1) year(-1) and the Fournier index ranged from 52.9 to 110.0 mm. The erosivity map showed that the study area can be broadly divided into three major erosion risk zones, and the Fournier index map was divided into four zones. Both methods revealed that the erosive force is severe in all study area and presented significant spatial correlation with each other. The erosive force in the country is concentrated mainly from May to November.
Keywords: rainfall erosivity; El Salvador Republic; GIS; USLE; R factor; soil conservation